2021
DOI: 10.3390/ijms22115852
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to the Mortality in Septic Shock Patients: From GWAS to the Identification of a Regulatory Variant Modulating the Activity of a CISH Enhancer

Abstract: The high mortality rate in septic shock patients is likely due to environmental and genetic factors, which influence the host response to infection. Two genome-wide association studies (GWAS) on 832 septic shock patients were performed. We used integrative bioinformatic approaches to annotate and prioritize the sepsis-associated single nucleotide polymorphisms (SNPs). An association of 139 SNPs with death based on a false discovery rate of 5% was detected. The most significant SNPs were within the CISH gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Variants were prioritized for the next stage if they satisfied having the same effect direction, a p<0.05 in both GEN-SEP recruitment periods, and a p<5.0x10 -7 after the meta-analysis of both periods. Association results of this first stage were also inspected to evaluate whether the variants or genes previously associated with sepsis mortality by other studies were also associated in GEN-SEP [15][16][17] .…”
Section: Genotyping and Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Variants were prioritized for the next stage if they satisfied having the same effect direction, a p<0.05 in both GEN-SEP recruitment periods, and a p<5.0x10 -7 after the meta-analysis of both periods. Association results of this first stage were also inspected to evaluate whether the variants or genes previously associated with sepsis mortality by other studies were also associated in GEN-SEP [15][16][17] .…”
Section: Genotyping and Statistical Analysesmentioning
confidence: 99%
“…However, the number of GWAS of sepsis or its complications is limited. To date, only three GWAS have been completed for sepsis mortality, although the likelihood of death for each patient over time was not considered [15][16][17] . Specifically, Rautanen et al 15 analysed 28-day mortality in patients with pneumonia, linking the FER tyrosine kinase (FER) gene variation with reduced risk for death from sepsis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Scherag and colleagues found that the top ranking variants associated with 28-day mortality from sepsis in their study were located in the Vacuolar Protein Sorting 13 Homolog A ( VPS13A ) gene [ 16 ]. Rosier and colleagues identified variants within the Cytokine Inducible SH2 Containing Protein ( CISH ) gene associated with mortality due to septic shock at day 7 or day 28 [ 17 ]. Finally, D’Urso and colleagues performed a GWAS of susceptibility and mortality in septic shock and polygenic risk score (PRS) analysis to assess the genetic overlap between septic shock risk/mortality with clinically relevant traits.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is influenced by genetic susceptibility. Inflammatory cytokine genes polymorphisms have been subject of study trying to explain the etiology of gynecological (leiomyomas) [12,13] and non-gynecological pathologies [14][15][16]. Although the contribution of genetics is well supported by many studies, they have not provided a simple and unambiguous answer to the etiology of endometriosis [17,18].…”
Section: Introductionmentioning
confidence: 99%